The Eucharist and history - Paterson, Torquil John Macleod (Rhodes University, Faculty of Divinity, Department of Divinity, 1990)
The thesis delineates an existential view of history, in which the eternal is defined as the ground of authentic human life which underlies true historical action. The historical is the manifestation of the eternal in the unique moment, and redefines the ahistorical conditions of human life. The ahistorical is the social and ideological conditioning of all human knowledge, usually presented in terms of various kinds of myth and ritual . The ahistorical contains both good and bad elements, but always has the tendency to become oppressive and is therefore constantly in conflict with the historical. The life of Jesus is described as the perfect expression of the eternal in true historical action, by which he came into conflict with the ahistorical of his society, as expressed in his death. By his resurrection, his life breaks the limitations of time and becomes transformative enabling all subsequent historical action. The eucharist is described as engaging with each of these dimensions of our existence. By being itself a ritual action containing a myth, the eucharist has an ahistorical form and therefore easily engages with the ahistorical dimensions of society. However, without a constant dialogue with the historical, the eucharist, as an ahistorical medium, can become allied to the dominant forces of society and become a means of oppression. The eucharist has at its centre the remembrance of the historical action of Jesus. True historical action in the present will result from a proper hermeneutic of the gospels. The eucharistic anamnesis must be regarded as part of the wider search for a relevant contemporary christology. The eucharist remembers the Last Supper, which is a parable of the whole life of Jesus and a prelude to his death and is a sacrifice in that it has a sacrificial form, and leads to our historical action, which will usually take the form of a conflict with the ahistorical and have sacrificial dimensions. The eternal only becomes present in our historical action, but the eucharist, by uniting us with the transforming power of the death and resurrection of Jesus, is a powerful aid to such action. The eucharist also provides the opportunity for resonances between Jesus and the ground of our being, thus enabling deep shifts of attitude and consciousness. Three fundamental prerequisites for human life are isolated and related to the eucharist: belonging, nurturing and giving. In order for the eucharist to ennable historical action is must hold these dimensions in tension. In its actual form it does this through the balance between the Words of Institution and the Epiclesis, which, in turn, provide the christological ground of the eucharist and relate this to the present through a particular pneumatology. The real presence is described by the thesis in a way which connects the eucharistic presence with the historical Jesus and leads to our historical action. Finally, some consequences of the thesis for Eucharistic practice are suggested. The relationship between the ahistorical form of the eucharist and the anamnesis is important. In this way the eucharist objectifies the ahistorical, reflects on this in terms of the historical action of Jesus, and reforms the ahistorical by modelling a response. This should lead to a more authentic expression of the eternal in the contemporary world
Keywords: Lord's Supper; History -- Religious aspects